2018
DOI: 10.3384/diss.diva-145095
|View full text |Cite
|
Sign up to set email alerts
|

Asset Liability Management for Tanzania Pension Funds

Abstract: Linköping 2018Front page images: (1) low magnification of snowflake like α-Al 2 O 3 formed on polished coating surface after 10 h oxidation; (2) blade-like transient Al 2 O 3 formed on shot-peened coating surface after 100 min oxidation; (3) spinel island formed on polished coating surface after 10 min oxidation. AbstractMCrAlY coatings (M=Ni and/or Co) have been widely used for the protection of superalloy components against oxidation and hot corrosion in the hot sections of gas turbines. The drive to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Akomea-Frimpong et al (2022) conducted a study examining the relationship between corporate governance practices and the performance of pension funds in Ghana, and revealed that corporate governance practices played a significant role in influencing the performance of pension funds. Mwakisisile (2018) conducted a study on Asset Liability Management (ALM) for Pension Funds in Tanzania, and revealed that the pension fund would face sustainability challenges in the long run due to the increased life expectancy of its members, and that in order to enhance the long-term sustainability of the Tanzania pension fund system, reforms were necessary in several areas such as contribution rate, investment guidelines, and the formulation of target levels (funding ratios) to assess the solvency situation . The study insisted that implementing such reforms would contribute to improving the overall sustainability of the pension system in Tanzania.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Akomea-Frimpong et al (2022) conducted a study examining the relationship between corporate governance practices and the performance of pension funds in Ghana, and revealed that corporate governance practices played a significant role in influencing the performance of pension funds. Mwakisisile (2018) conducted a study on Asset Liability Management (ALM) for Pension Funds in Tanzania, and revealed that the pension fund would face sustainability challenges in the long run due to the increased life expectancy of its members, and that in order to enhance the long-term sustainability of the Tanzania pension fund system, reforms were necessary in several areas such as contribution rate, investment guidelines, and the formulation of target levels (funding ratios) to assess the solvency situation . The study insisted that implementing such reforms would contribute to improving the overall sustainability of the pension system in Tanzania.…”
Section: Empirical Literaturementioning
confidence: 99%
“…Regardless of of such efforts taken so far, still the government is far from achieving the Universal Health Coverage (UHC) due to a small population that is currently granted with access to health services as only few people are currently under health insurance coverage. To date, out of the country population (57,637,628) (Mwakisisile & Mushi, 2020) only 8 percent is enrolled with NHIF, 5.4 percent is covered under CHF, 0.3 percent covered by SHIB (NSSSF) and 1 percent being enrolled under private health insurance companies (Kibambo, 2021). This leads to the total of 14.7 percent as country coverage.…”
Section: Introductionmentioning
confidence: 99%